Eksplorasi Penerapan Diferensiasi Pembelajaran pada Pengajaran Bahasa Inggris - Muhayyang, Maemuna; Noni, Nurdin; Farahdiba, Syarifah; G, Hasriani (Juwara: Jurnal Wawasan dan Aksara, 2024)
This study aims to explain teachers' perspectives on differentiated instruction and its implementation in English language teaching. The research employed a descriptive qualitative approach with purposive sampling, involving three English teachers from MTs N Ma’rang, Pangkep (two civil servant teachers and one non-civil servant teacher). Data were collected through interviews and observations and analyzed in four stages: data collection, condensation, display, and conclusion drawing. The findings reveal that the teachers understand differentiated instruction as a model that adapts materials to students' characteristics. They recognize the importance of aligning instruction with students' profiles, both physiologically and psychologically. For its implementation, the three teachers focused on three key elements: content, process, and product, which were adjusted from the initial to the final phases of learning. Materials were designed based on students' levels of knowledge, understanding, and learning styles identified through diagnostic evaluations and direct observations. In conclusion, the application of differentiated instruction enables teachers to meet students' needs more effectively, thereby supporting the process of learning English as a foreign language. This approach provides a relevant and meaningful learning experience for students with diverse individual characteristics.